Insulin secretion - Gheibi, Sevda; Ghasemi, Asghar (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
Nitric oxide (NO) is a gas that serves as a ubiquitous signaling molecule participating in physiological activities of various organ systems. Nitric oxide is produced in the endocrine pancreas and contributes to synthesis and secretion of insulin. The potential role of NO in insulin secretion is disputable – both stimulatory and inhibitory effects have been reported. Available data indicate that effects of NO critically depend on its concentration. Different isoforms of NO synthase (NOS) control this and have the potential to decrease or increase insulin secretion. In this review, the role of NO in insulin secretion as well as the possible reasons for discrepant findings are discussed. A better understanding of the role of NO system in the regulation of insulin secretion may facilitate the development of new therapeutic strategies in the management of diabetes.
the nitric oxide controversy
EXCLI Journal;Vol. 19 2020
Keywords: Nitric oxide; Insulin secretion; Insulin synthesis; 610